High resolution measurement network of global horizontal and tilted solar irradiance in southern Germany with a new quality control scheme. (1st January 2022) - Lorenz, Elke; Guthke, Philipp; Dittmann, Anna; Holland, Nicolas; Herzberg, Wiebke; Karalus, Steffen; Müller, Björn; Braun, Christian; Heydenreich, Wolfgang; Saint-Drenan, Yves-Marie
Abstract: Upscaling techniques are applied to estimate the total power feed-in by PV systems in control areas by grid operators. In order to improve the real-time upscaling of PV power production in the control area of the German transmission system operator TransnetBW we set up a network of 40 solar irradiance measurement stations in southern Germany. The measurement stations consist of a pyranometer, measuring global horizontal irradiance, and three silicon cells oriented east, south, and west with tilt angles of 25°, measuring global tilted irradiance. Irradiance values in minute resolution are transferred in near real-time. In order to ensure a good quality of our data we have developed a new quality control scheme exploiting the sensors with different orientations. Starting with data from September 2020, we will make the quality controlled minute-resolution measurements publicly available on a monthly basis. Highlights: Horizontal and tilted global irradiance measurements for 40 sites. Publication of data set in minute resolution with monthly updates. New quality control scheme for tilted irradiance. Machine learning for detection of shading and orientation.